Pale yellow-to-dark blue electrochromic film produced by oxidation electropolymerization of a triphenylamine derivative with an enhanced electron-withdrawing group. (5th September 2021) - Pi, Qiaozhen; Li, Lijun; Qiu, Dongfang; Wang, Hongwei; Cheng, Xinfeng; Yang, Chunxia; Zhao, Qian; Zhou, Mingdong
Graphical abstract: The redox film prepared by oxidative electropolymerization of the triphenylamine derivative linking a doubly N -methylated terpyridine-like unit shows significant colour change from pale yellow to dark blue with high optical contrast, fast response times, high coloration and bleaching efficiencies. Highlights: Much enhanced intramolecular D-A interaction. TPA-triggered electropolymerization mechanism to efficiently form a redox polymer film. Dual-wavelength EC behaviour in the VIS-NIR spectral region. Significant colour change from pale yellow to dark blue under + 1.2 V with high optical contrast (Δ T % = 78%), fast response times, high coloration and bleaching efficiencies. Abstract: The triphenylamine derivative with a terpyridine-like unit, {4-[ p -(N, N-diphenylamino)-phenyl]-2, 6-di(pyrazin-2-yl)pyridine}, and its doubly N -methylated salt have been successfully synthesized and characterized. The salt with much enhanced intramolecular D-A interaction shows a remarkable bathochromical shift of its absorption bands and a fluorescence quenching effect. And its oxidative electropolymerization film with tunable thickness and non-diffusion controlled redox behavior has also been obtained by cyclic voltammetry on the working ITO electrode. The film possesses an independent dual-wavelength response in visible (400–850 nm) and near-infrared (850–2100 nm) spectral regions under different voltages. The low-voltage-controlled electrochromism displays significant color change from pale yellow to dark blue (Δ T % = 78%) with fast response time (6 s for the coloration step and 3 s for the bleaching step), high coloration and bleaching efficiencies (363.7 and 238.5 C -1 ·cm 2 ) at λ max  = 730 nm between −0.2 and + 1.2 V.